Wind Turbine Blade LPS Design Process Revisited—Leveraging on the Latest Knowledge from Actual Lightning Measurements in Wind Turbines - Søren Find Madsen; Stephan Vogel; Javier Lopez; Lisa Carloni (Machines, 2023)
The present paper addresses some recent lightning measurements with the in actual wind turbines, to demonstrate the amount of data that is currently collected, and the information provided. Basic statistical analysis is conducted on the 2603 lightning waveforms obtained, and implications for design and verification processes for blades are suggested. Some reflections on the increased industry openness are shared, which is already benefitting the general understanding of lightning exposure, and the future standards on the topic.